Deficient mismatch repair/microsatellite unstable colorectal cancer: Diagnosis, prognosis and treatment. (November 2022) - Taieb, Julien; Svrcek, Magali; Cohen, Romain; Basile, Debora; Tougeron, David; Phelip, Jean-Marc
Abstract: Microsatellite unstable (MSI) colorectal cancers (CRCs) are due to DNA mismatch repair (MMR) deficiency and occurs in15% of non-metastatic diseases and 5% in the metastatic setting. Nearly 30% of MSI CRCs occur in a context of constitutional mutation of the MMR system (Lynch syndrome). Others are sporadic cancers linked to a hypermethylation of the MLH-1 promoter. The pathogenic alterations of MMR genes lead to the accumulation of frequent somatic mutational events and these tumours arbour a high antigen burden and are highly infiltrated with cytotoxic T-cell lymphocytes. Microsatellite instability/DNA mismatch repair deficiency (MSI/dMMR) status has prognostic and predictive implications in non-metastatic and metastatic CRCs. The prognostic value of MSI status in non-metastatic CRCs has been studied extensively, yet the data are more limited for its predictive value in terms of adjuvant chemotherapy efficacy. In both cases (metastatic and non-metastatic settings) treatment with immune check-point inhibitors (ICIs) have shown a remarkable effectiveness in the context of MSI/dMMR status. Indeed, recent data from prospective cohorts and randomised trials have shown a dramatical improvement of survival with immunotherapy (programmed death-ligand 1 [PD-(L)1]   cytotoxic T-lymphocyte-associated antigen 4 [CTLA-4] blockage) in metastatic or non-metastatic MSI/dMMR CRC. In this review we report and discuss how and for whom to test for the MSI/dMMR phenotype, as well as the prognostic value of this phenotype and the new treatment recommendations options for this unique CRC population. Despite their efficacy, primary and secondary resistance to immune checkpoint inhibitors (ICIs) are observed in more than 50% MSI-H/dMMR CRC patients and in the future how to identify these patients and to overcome resistance will be an important challenge. Highlights: Microsatellite unstable (MSI) status has to be tested in all colorectal cancer (CRC) stages for Lynch syndrome screening. MSI patients represent 10–20% of localised and 5% of metastatic CRCs. Localised MSI CRCs have a better prognosis than localised microsatellite stable (MSS) CRCs. Immunotherapy is very efficient in most MSI CRCs.